Mercury levels in Southern Ocean squid: Variability over the last decade. (January 2020) - Seco, José; Xavier, José C.; Brierley, Andrew S.; Bustamante, Paco; Coelho, João P.; Gregory, Susan; Fielding, Sophie; Pardal, Miguel A.; Pereira, Bárbara; Stowasser, Gabriele; Tarling, Geraint A.; Pereira, Eduarda
Abstract: The concentrations of total and proportions of organic mercury were measured in tissues of 355 individuals of 8 species of Southern Ocean squid ( Alluroteuthis antarcticus, Bathyteuthis abyssicola, Filippovia knipovitchi, Galiteuthis glacialis, Gonatus antarcticus, Kondakovia longimana, Psychroteuthis glacialis and Slosarczykovia circumantarctica) . Squid were caught around South Georgia (Scotia Sea) during 5 cruises, between the austral summers of 2006/07 to 2016/17 to evaluate temporal changes in bioaccumulation and tissue partitioning. Total mercury concentrations varied between 4 ng g −1 and 804 ng g −1 among all tissues. Net accumulation of mercury in muscle with size was observed in A. antarcticus, B. abyssicola and P. glacialis, but no relationship was found for S. circumantarctica and lower concentrations were observed in larger individuals of G. glacialis. Muscle tissues had the highest mercury concentrations in the majority of species, except for F. knipovitchi for which the digestive gland contained highest concentrations. In terms of the percentage of organic mercury in the tissues, muscle always contained the highest values (67%–97%), followed by the digestive gland (22%–38%). Lowest organic mercury percentages were found consistently in the gills (9%–19%), suggesting only low levels of incorporation through the dissolved pathway and/or a limited redistribution of dietary organic mercury towards this tissue. Overall, results are indicative of a decreasing trend of mercury concentrations in the majority of analysed species over the last decade. As cephalopods are an important Southern Ocean trophic link between primary consumers and top predators, these changes suggest decreasing mercury levels in lower trophic levels and an alleviation of the mercury burden on higher predators that consume squid. Highlights: Hg decreases over the last decade, in most of the analysed squid species. There is an even partitioning of total Hg among squid tissues. Organic Hg was higher in muscle, reflecting the role of diet in bioaccumulation.